AL MAWARDI’S SOCIAL CONTRACT THEORY (STUDY OF AL MAWARDI'S POLITICAL THOUGHT) - Mauliana Maghfiroh (UIN Walisongo Semarang, 2023)
As social beings, humans depend on each other to meet their needs and interests. For this reason, a definite regulatory structure (institutionalization) is needed to minimize and overcome various problems that arise. Al-Mawardi is one of the most interesting Islamic political thinkers to discuss. The basic concept of al-Mawardi's political thought is the origin of the social contract theory. Through qualitative research methods through literature studies, this article will discuss al-Mawardi's social contract theory based on his political thoughts. The discussion in this article starts from a discussion of al-Mawardi's biography, al-Mawardi's main thoughts regarding the state and leadership, as well as the relationship between the ruler and the people which later became the social contract theory.